Separation of dyes with reversible aqueous biphasic systems - Ferreira, Ana Maria da Conceição (2013)
The main objective of this work conveys on the study of reversible aqueous two-phase systems (ATPS), constituted by ionic liquids (ILs), and their potential application for the selective separation of dyes mainly used in the textile industry. The textile manufacturing is one of the main industries which discharges a heavy load of chemicals, especially large contents of dyes during the dying process through wastewaters, which results in severe environmental and economic concerns. In this context, this work focuses on the applicability of reversible ATPS, as well as on the development of more benign systems than those studied hitherto, as an alternative technique for the removal of dyes from wastewaters. Additionally, special attention was also given to the understanding of the molecular mechanisms which rule the partitioning of dyes between the coexisting phases of ATPS. IL-based ATPS display a widespread applicability in the extraction, concentration and purification of a large range of compounds, including dyes. Thus, this work started with investigations on the extraction of a set of dyes (chloranilic acid, indigo blue and sudan III) using more conventional ATPS composed of ILs and an organic/inorganic salt. At this stage, the influences of the IL chemical structure, the salting-out ability of the salt employed and the consequent pH of the aqueous medium were evaluated by the dyes extraction efficiencies. The results obtained reveal that a proper selection of the IL and salt can lead to the complete extraction of the three dyes studied for the IL-rich phase in a single-step procedure. After demonstrating the high capacity of ATPS formed by ILs to extract dyes from aqueous phases, it was studied the applicability of pH-triggered reversible ATPS in the selective separation of organic and inorganic dyes (sudan III and pigment blue 27). The reversibility of this type of ATPS was achieved by the manipulation of the speciation of the organic salt used. The results obtained confirm the reversibility behaviour of ATPS by a pH-driven phenomenon, at least for three times, as well as their selective separation capability with both dyes being extracted for opposite phases. Finally, and after demonstrating the existence of reversible pH-triggered ATPS, mixtures of a polymer and cholinium-based ILs combined with anions derived from carboxylic acids were investigated, foreseeing the search of more benign and biocompatible systems. The reversibility of these systems was achieved with the speciation of the IL anion as a function of the pH. These systems were finally evaluated in what concerns their performance for the extraction and selective separation of dyes (sudan III, pigment blue 27 and pigment 29), and the study revealed that IL-polymer systems are capable of selectively extract organic and inorganic dyes for opposite phases.